Functional Structural Theory and Economic Empowerment among MSMEs in Rural Areas - Yanti, Lesti Heri; Wijayanti, Ayu; Anggraini, Ayu; Emilda, Syahria; Sari, Rosi Puspita (Lembaga Penelitian dan Pendidikan Mandala, 2025)
MSMEs are one of the economic sectors that have a strategic role in the village economy, the role of MSMEs in the economy is also influenced by various factors including village potential, infrastructure, government policies, and synergy between village MSMEs, Therefore, the Makassar Maju College of Economics created a main work program for the Socialization of